IMPLEMENTASI HADIS PEREMPUAN MELAKUKAN PERJALANAN TANPA MAHRAM BERTENTANGAN DENGAN ATURAN BARU ARAB SAUDI MEMBOLEHKAN WANITA PERGI TANPA MAHRAM - Abdurrozak, Abdurrozak; Maulana riefq; Regiansyah (Aqwal: Journal of Qur'an and Hadis Studies, 2020)
The hadith about maẖram for a woman's journey is one of the social phenomena debated in Islam. Some read it through a textual approach and some read it in a contextual framework. For this reason, a new alternative reading is needed that is felt responsive in the contextual realmwhen discussing the hadith, with the new Saudi Arabian rules regarding allowing women to go alone without a mahram. The result is that the role of maẖram in this hadith is a form of concrete prevention for women against all violence that will befall them. Such prevention is not only carried out by the woman's immediate family but also by instruments created by the state and can also be referred to as maẖram, so this approach encapsulates its meaning contextually but does not leave the maẖram ati textually.